Uruguay : Third Review Under the Stand-By Arrangement and Request for Modification and Waiver of Nonobservance of Performance Criteria; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2006)
Strong economic policies and a supportive external environment have contributed to rapid growth, low inflation, strengthened external position, and an improved debt structure helping Uruguay perform well under the Stand-By Arrangement. Executive Directors commended the fiscal and monetary polices and urged to maintain exchange rate flexibility. They emphasized that restructuring of public banks would contain contingent fiscal liabilities. They appreciated the efforts to strengthen tax administration, and agreed that continued strong macroeconomic polices and progress with structural reforms will raise Uruguay's growth prospects.